Bladder leiomyoma masquerading as a ureterocele. Issue 6 (15th June 2021) - Grice, Peter; O'Dowd, Sophie; Parkinson, Richard; Bazo, Alvaro
Abstract : We present a unique case of bladder leiomyoma that was mistakenly diagnosed as a ureterocele. The delay in diagnosis meant ongoing significant voiding lower urinary tract symptoms, which could have been avoided. This was eventually successfully treated by transurethral resection. Leiomyoma is the most common benign bladder mass and should be considered in the differential diagnosis when a smooth mass with normal overlying mucosa is seen on cystoscopy or a homogeneous, low density bladder mass is seen on cross-sectional imaging. Despite the benign nature of the lesion, leiomyoma can convey significant morbidity to the patient.